Genetic testing for pheochromocytoma - Karasek, David; Frysak, Zdenek; Pacak, Karel (Current hypertension reports, 2010)
Pheochromocytomas (PHEOs) and paragangliomas (PGLs) are rare, catecholamine-producing tumors that are usually sporadic. However, about 30% of these tumors have been identified as being of inherited origin. To date, nine genes have been confirmed as participating in PHEO or PGL tumorigenesis. Germline mutations were found in 100% of syndromic cases and in about 90% of patients with positive familial history. In nonsyndromic patients with apparently sporadic tumors, genetic mutations have been found in up to 27%, and genetic testing is now recommended for all patients with PHEOs and PGLs. Patients with syndromic lesions, a positive family history, or both should be tested for the appertaining gene. Recent discoveries have shown that the order of tested genes in nonsyndromic, nonfamilial cases can be based on histologic evaluation, location, and the biochemical phenotype of PHEOs and PGLs--the "rule of three." Identification of a gene mutation may lead to early diagnosis and treatment, regular surveillance, and a better prognosis for patients and their relatives.
Keywords: Humans; asymptomatické nemoci; lidé středního věku; Adrenal Gland Neoplasms; Pheochromocytoma; mnohočetná endokrinní neoplazie typ 2A; zárodečné mutace; dospělí; výsledek terapie; katecholaminy; Early Detection of Cancer; lidé; sukcinátdehydrogenasa; časná detekce nádoru; Adult; Germ-Line Mutation; Middle Aged; Asymptomatic Diseases; Treatment Outcome; Multiple Endocrine Neoplasia Type 2a; nádory nadledvin; Catecholamines; genetické testování; Genetic Testing; míra přežití; Succinate Dehydrogenase; feochromocytom; Survival Rate